Ein stilles Credo J.S. Bachs - Overstolz, Christian (Schwabe Verlag, 2018)
This book is a result of the author's long engangement with the prelude and fugue in A major of Johann Sebastian Bach. This work's origins lie deep in theology. The author tries to prove that in this piece of music, Bach expresses point by point the credo as we know it from Bach's Mass in B minor.